A reabilitação dos afetos: uma incursão no pensamento complexo de Edgar Morin - Allegro, Luís Guilherme Vieira (2007)
This dissertation aims at following the emergence of issues concerning human feelings through the works of Edgar Morin by delving into the vortex which makes up mankind and going as far as the ethics and the utopia unfolded by the complexity theory. Love will also be addressed as part of these reflections